Silicon ceiling. (Economist, 2026)
The article projects that the bottleneck in the artificial intelligence (AI) industry will get worse as demand rises faster than technology companies can add capacity. Issues discussed include opposition to the construction of data centres, shortage of chips to fill data centres, difficulty of obtaining AI processors, shortages of high-band memory chips and central-processing units, and the lesser investment of companies along the AI supply chain compared to hyperscalers.